PERHITUNGAN PARAMETER SCALED-DOWN UNTUK PERANGKAT KERAS MODEL SISTEM TENAGA LISTRIK - Herris Yamashika; Mahyessie Kamil (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
Abstract: This article provides reduced calculation parameters for power system transmission models. Transmission parameters modeled are single transmission lines using ACSR 1x241.7 mm2 (Hawk), with parameter values of 0.129  / km for resistance, 0.4049 km / km for reactance, and admission of 2.533 33S / km. Minimized parameters are calculated using current, voltage, impedance, and power scale factors. A 150 kV transmission line with a current capacity of 100 A at 50 Hz system frequency, scaled to a voltage of 15 V and 5 A. The results obtained from the calculation are scaled down to 0.258 m / km for resistance, 0.81 m / km for reactance, and admintance 1.27 mS / km. The load is connected to a 20 kV system with a current capacity of 500 A, and scaled to 2 V and 5 A. The reduced impedance value obtained is 0.02887 for active power, and 1.2252 mH for reactive power. Keywords: lower scale model, electric power system model, electric power system